Development of a New Reporter Gene System-dsRed/Xanthine Phosphoribosyltransferase-Xanthine for Molecular Imaging of Processes Behind the Intact Blood-Brain Barrier - Mikhail Doubrovin; Vladimir Ponomarev; Inna Serganova; Suren Soghomonian; Tadashi Myagawa; Tatiana Beresten; Lyudmila Ageyeva; Michel Sadelain; Jason Koutcher; Ronald G Blasberg; Juri G. Gelovani Tjuvajev (Molecular Imaging)
We report the development of a novel dual-modality fusion reporter gene system consisting of Escherichia coli xanthine phosphoribosyltransferase (XPRT) for nuclear imaging with radiolabeled xanthine and Discosoma red fluorescent protein for optical fluorescent imaging applications. The dsRed/XPRT fusion gene was successfully created and stably transduced into RG2 glioma cells, and both reporters were shown to be functional. The level of dsRed fluorescence directly correlated with XPRT enzymatic activity as measured by ribophosphorylation of [ 14 C]-xanthine was in vitro ( K i = 0.124 ± 0.008 vs. 0.00031 ± 0.00005 mL/min/g in parental cell line), and [ * ]-xanthine octanol/water partition coefficient was 0.20 at pH = 7.4 (log P = 0.69), meeting requirements for the blood-brain barrier (BBB) penetrating tracer. In the in vivo experiment, the concentration of [* C]-xanthine in the normal brain varied from 0.20 to 0.16 + 0.05% dose/g under 0.87 + 0.24% dose/g plasma radiotracer concentration. The accumulation in vivo in the transfected flank tumor was to 2.4 ± 0.3% dose/g, compared to 0.78 ± 0.02% dose/g and 0.64 ± 0.05% dose/g in the control flank tumors and intact muscle, respectively. [ 14 C]-Xanthine appeared to be capable of specific accumulation in the transfected infiltrative brain tumor (RG2-dsRed/XPRT), which corresponded to the 585 nm fluorescent signal obtained from the adjacent cryosections. The images of endogenous gene expression with the “sensory system” have to be normalized for the transfection efficiency based on the “beacon system” image data. Such an approach requires two different “reporter genes” and two different “reporter substrates.” Therefore, the novel dsRed/XPRT fusion gene can be used as a multimodality reporter system in the biological applications requiring two independent reporter genes, including the cells located behind the BBB.